Dynamic Model Analysis of Waste Absorption Carrying Capacity Values ​​in Semi-Intensive Shrimp Ponds - Wafi, Abdul; Ariadi, Heri; van Minnen, Tjalf (Biosaintifika: Journal of Biology & Biology Education, 2025)
The stable availability of dissolved oxygen in semi-intensive shrimp ponds plays a crucial role in the sustainability of the aquaculture system. The objective of this study is to determine the trend of the dissolved oxygen carrying capacity for waste absorption during shrimp farming in a semi-intensive system. The method used in this research is causal-ex-post facto research with data analysis using dynamic modeling systems. The results show that the water quality parameters tend to be stable, except for organic matter (51.82–115.02 mg/L). The semi-intensive shrimp farming system demonstrates relatively high harvest production, attributed to rapid shrimp growth despite limited feed management, resulting in profitable outcomes. Dynamic modeling reveals that increased biomass correlates with higher waste output, affecting the dissolved oxygen (DO) carrying capacity. Modeling also shows a moderate and fluctuating waste runoff pattern, indicating variable DO consumption. An important finding from this research is that we can control the water's carrying capacity for waste adsorption by determining the ideal cultivation system. The study concludes that DO carrying capacity follows a linear relationship with waste load; as waste increases, oxygen demand rises accordingly to support organic matter decomposition and ecosystem balance. These findings highlight the importance of managing waste to maintain optimal oxygen levels in semi-intensive systems. The conclusions of this research are important to be used as a source for coastal area management studies based on carrying capacity.